Determinantes moleculares da diferenciação inicial do cérebro em castas de abelhas Apis mellifera - Vieira, Joseana (2014)
Brain development is driven by both genetic and environmental factors. Among the latter, diet has been considered to play a key role. We have recently shown that in honeybees, queen larvae, which are fed on copious amounts of royal jelly, experience larger and faster brain development than workers. We have also shown that this differential morphogenesis is evident from the 4th larval (L4) stage on. This finding implies that a high nutritional input drives nervous system development. Recent studies have shown that the composition of royal and worker jellies differs, leading to differences in gene expression patterns. Some miRNAs are more abundant in worker jelly than in royal jelly during early larval development, suggesting a role for these small molecules in caste determination. Since there are no morphological differences between queens‘ and workers‘ brain before L4, we hypothesized that the first observed differences are molecularly promoted early in development. Herein we aimed at identifying nutritionally-responsive genes in brains of queens and workers at the 3rd larval stage. Using RNA-Seq, we identified 60 differentially expressed genes (DEG), 31 upregulated in workers and 29 in queens. Among the genes upregulated in queens, seven are known to be associated to neuronal activity: aromatic-L-amino-acid decarboxylase-like, Spatzle-2, three serine proteases (SP25, SP33 and SPH41), apolipoprotein D-like, and forked. Eight out of 31 genes upregulated in workers have functions associated to brain growth impairment or are relevant for the development of caste-specific traits: chymotrypsin inhibitor-like, chymotrypsin inhibitor, GB51989 (with a pacifastin conserved domain), three hexamerins (hex-110, -70c and -70b), cytochrome P450 9Q1 and nesprin 1 -like. In addition, twelve genes, out of the 60, are located on chromosome 15, thus suggesting co-regulation of this group of genes. Complex network analysis suggests that many of the DEG are targets of miRNAs present in the jellies and, thus, are part of a complex pathway leading to the development of the observed brain diphenism in honeybee castes